Short Communication: Species composition and density of mangrove forest in Kedawang Village, Pasuruan, East Java, Indonesia - WAHYU ISRONI; R ADHARYAN ISLAMY; MOHAMAD MUSA; PUTUT WIJANARKO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Isroni W, Islamy RA, Musa M, Wijanarko P. 2019. Short Communication: Species composition and density of mangrove forest in Kedawang Village, Pasuruan, East Java. Biodiversitas 20: 1688-1692. Mangrove is one of ecosystems located in estuary and shallow coastal waters and its existence has a significant role for life. The aim of this study was to identify species composition and density of mangrove forest in Kedawang village, Nguling Sub-district, Pasuruan District, East Java, Indonesia. Survey method using belt transects was carried at three sampling points. Results of this study showed that mangrove vegetation in Kedawang includes five species from three families, namely Avicenniaceae (Avicennia alba and Avicennia marina), Rhizophoraceae (Rhizophora apiculata and Rhizophora mucronata), and Sonneratiace (Sonneratia alba). At sampling point 1, A. alba dominated with a density of 37 individuals/ha at tree level, 380 individuals/ha at pole level and 3100 individuals/ha at stake level. At sampling point 2, the tree level was dominated by A. alba with 142 individuals/ha, while R. mucronata dominated the pole and stake level with 1300 and 1467individuals/ha, respectively. At sampling point 3, the pole and stake level was dominated by A. alba with 167 and 933 individuals/ha respectively, while A. marina dominated the sapling level with 800 individuals/ha. At all stations, the density at stake level is greater than that tree level. Therefore, it is necessary to carry out conservation efforts in the form of protection combined with restoration by enrichment planting at all study locations to increase the diversity and density of mangrove vegetation.